(untitled) (Dhaka University Journal of Business Studies, 2021)
The importance of bilateral trade analysis between Bangladesh and China is increasing as Bangladesh constantly searches for opportunities to reduce the enormous trade deficit with China. This study analyzes Bangladesh’s export to China using the famous ‘Trade Gravity Model.’ The study examined Bangladesh’s exports to China from 1999 to 2020 using factors: Gross Domestic Product (GDP) of Bangladesh, Gross Domestic Product (GDP) of China, Population of Bangladesh, Population of China, Relative Distance between Bangladesh and China, Weighted Average Tariff Rate imposed by China and Relevant Trade Agreements between Bangladesh and China. The findings suggest that the exports of Bangladesh to China will rise with the increase of GDPs of Bangladesh and China, the populations of Bangladesh and China, and with the growth of number of trade agreements between Bangladesh and China. The study also shows that Bangladesh’s export to China will decrease with the increase of tariffs imposed by China on imports from Bangladesh and length of distance covered by the export order. The study’s findings provide policy implications for Bangladesh towards its successful graduation from the Least Developed Countries (LDCs) status. Journal of Business Studies, Vol. XLII, No. 1, April 2021 Page 73-86